Steroid‐Responsive Encephalitis in Coronavirus Disease 2019. Issue 2 (9th June 2020) - Pilotto, Andrea; Odolini, Silvia; Masciocchi, Stefano; Comelli, Agnese; Volonghi, Irene; Gazzina, Stefano; Nocivelli, Sara; Pezzini, Alessandro; Focà, Emanuele; Caruso, Arnaldo; Leonardi, Matilde; Pasolini, Maria P.; et al.
Abstract : Coronavirus disease 2019 (COVID‐19) infection has the potential for targeting the central nervous system, and several neurological symptoms have been described in patients with severe respiratory distress. Here, we described the case of a 60‐year‐old patient with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection but only mild respiratory abnormalities who developed an akinetic mutism attributable to encephalitis. Magnetic resonance imaging was negative, whereas electroencephalography showed generalized theta slowing. Cerebrospinal fluid analyses during the acute stage were negative for SARS‐CoV‐2, positive for pleocytosis and hyperproteinorrachia, and showed increased interleukin‐8 and tumor necrosis factor‐α concentrations. Other infectious or autoimmune disorders were excluded. A progressive clinical improvement along with a reduction of cerebrospinal fluid parameters was observed after high‐dose steroid treatment, thus arguing for an inflammatory‐mediated brain involvement related to COVID‐19. ANN NEUROL 2020;88:423–427.